THE NEOPLASTIC POTENTIALITIES OF MOUSE EMBRYO TISSUES : IV. LUNG ADENOMAS IN BABY MICE AS RESULT OF PRENATAL EXPOSURE TO URETHANE - Smith, William E. (The Rockefeller University Press, 1948)
The observation that adenomas develop very rapidly in the pulmonary tissue of mouse embryos implanted together with methylcholanthrene, in adult animals, has led to tests of the neoplastic potentialities of this tissue in utero. C strain females in the latter half of pregnancy were injected with urethane and the lungs of their young were searched for adenomas. None could be perceived with certainty in embryos at term or in mice just born, but they were several times found 3 days after birth and they were frequent and much larger in 10-day-old animals. The controls showed none. After 60 to 70 days they were often visible in the gross. Corroboratory findings were obtained in A mice. No parallelism could be perceived in the incidence of the tumors in mothers and offspring. The adenomas arose from tissue devoid of any sign of preliminary local disturbance. Mitoses were abundant in them and they grew rapidly for a while, but within 2 months cell division had almost ceased. By this time however many of the neoplasms were as big as any adenomas in the urethanized mother animals and in some instances twice as big. While growing fast they underwent little differentiation, but this took place when proliferation slowed and in consequence the tumors came to have the morphology of the spontaneous and induced adenomas of adults. The neoplastic cells were derived from alveolar elements, yet in proportion as differentiation of them occurred they came to resemble the epithelial cells lining the small bronchioles. Occasionally the resemblance to bronchial epithelium was complete, save that the cytoplasm of the tumor cells was slightly basophilic. The following conclusions seem justified:— 1. The injection of urethane into pregnant female mice of the C strain frequently initiates the development forthwith of pulmonary adenomas in the young she is carrying. 2. Some of the pulmonary cells of mouse embryos well along toward term possess the ability to be neoplastic. 3. The adenomatous change finds swift expression in young creatures because of conditions implicit in their youth. The rapid proliferation of the tumor cells is almost entirely due to these conditions, not to the neoplastic state as such. 4. Adenomatous change prior to birth is intrinsically the same process as that occurring in the adult creature. 5. The adenomatous state does not prevent the cells of young mice from undergoing the maturation that takes place in normal elements of the same sort as the organism grows older. Though the proliferative activity natural to youth and the unnatural activity consequent on neoplastic change are summated in the young organism, they still are separable.